Investigating the subjective and objective factors influencing teenagers' school travel mode choice – An integrated choice and latent variable model. (August 2015) - Kamargianni, Maria; Dubey, Subodh; Polydoropoulou, Amalia; Bhat, Chandra
Abstract: In this paper, we apply Bhat and Dubey's (2014) new probit-kernel based Integrated Choice and Latent Variable (ICLV) model formulation to analyze children's travel mode choice to school. The new approach offered significant advantages, as it allowed us to incorporate three latent variables with a large data sample and with 10 ordinal indicators of the latent variables, and still estimate the model without any convergence problems. The data used in the empirical analysis originates from a survey undertaken in Cyprus in 2012. The results underscore the importance of incorporating subjective attitudinal variables in school mode choice modeling. The results also emphasize the need to improve bus and walking safety, and communicate such improvements to the public, especially to girls and women and high income households. The model application also provides important information regarding the value of investing in bicycling and walking infrastructure.